2020
DOI: 10.1186/s13071-020-04445-z
|View full text |Cite
|
Sign up to set email alerts
|

The life-cycle of Toxoplasma gondii reviewed using animations

Abstract: Toxoplasma gondii is a protozoan parasite that is the causative agent of toxoplasmosis, an infection with high prevalence worldwide. Most of the infected individuals are either asymptomatic or have mild symptoms, but T. gondii can cause severe neurologic damage and even death of the fetus when acquired during pregnancy. It is also a serious condition in immunodeficient patients. The life-cycle of T. gondii is complex, with more than one infective form and several transmission pathways. In two animated videos, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
90
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(129 citation statements)
references
References 74 publications
(77 reference statements)
0
90
0
3
Order By: Relevance
“…T. gondii and T. brucei occupy two different ecological niches. T. gondii is an intracellular parasite that resides and proliferates within a parasitophorous vacuole that is located within the cytoplasm of a host cell [ 8 , 9 ]. In contrast, T. brucei is an extracellular parasite, with the mammalian bloodstream forms undergoing antigenic variation and surviving in the blood and lymphatic vessels prior to crossing the blood–brain barrier, where they also remain in the extracellular space [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…T. gondii and T. brucei occupy two different ecological niches. T. gondii is an intracellular parasite that resides and proliferates within a parasitophorous vacuole that is located within the cytoplasm of a host cell [ 8 , 9 ]. In contrast, T. brucei is an extracellular parasite, with the mammalian bloodstream forms undergoing antigenic variation and surviving in the blood and lymphatic vessels prior to crossing the blood–brain barrier, where they also remain in the extracellular space [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cats after getting infected start oocyst shedding, typically for a period of 1–2 weeks in primary infections [ 41 ] and re-shedding reactivate in super infection with other feline diseases, malnourishment and during the immunosuppression [ 42 ]. The global burden of human toxoplasmosis is remarkably high and about 60% people of population approximately one to two billion population are reported to be infected with illness [ 43 , 44 ]. There is established evidence proving that naive cats fed with RMBD diets have higher seropositivity rates and shed a large number of oocysts of T. gondii in their faeces [ 3 ] and a study in Netherland, found out 2 products (6%) out of 35 commercial frozen RMBD's samples positive for T. gondii [ 13 ].…”
Section: Life Cycle Of Some Parasites From Raw Meat Feeding Involving Pets and Humansmentioning
confidence: 99%
“…In Toxoplasma gondii, macrogametes have an oval shape, a single nucleus, endoplasmic reticulum, mitochondria, lipid bodies, amylopectin inclusions, and two types of wallforming bodies. Microgametes are elongated; they display a condensed nuclear chromatin, two flagella in the anterior region, and a mitochondrion located at the base of the flagella [78,79]. The fusion of micro-and macrogamete leads to the formation of an oocyst that is released into the intestinal lumen of the definitive host.…”
Section: Subclass Coccidiasinamentioning
confidence: 99%